2018
DOI: 10.4028/www.scientific.net/msf.910.9
|View full text |Cite
|
Sign up to set email alerts
|

Wire Mesh/Ceramic Particle Reinforced Aluminium Based Composite Using Explosive Cladding

Abstract: In this study, dissimilar grade aluminium plates were explosively cladded by placing a wire mesh/ceramic particle between them. The stainless steel 316 mesh with 90o orientation and SiCp (1.5 volume %) are employed to enhance the mechanical properties of the aluminium composites. Microhardness and microstructure of the explosively cladded composite materials were evaluated. Significant improvement in the microhardness of the wire mesh/ceramic particle reinforced aluminium composite is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…No significant deformation of the base substrate was found after the explosive detonation [ 75 , 78 ]. Lalu Gladson Robin et al reported that the coating layers cladded with the help of explosion cladding possess excellent hardness even at the coating-substrate interface [ 76 ]. A comparative analysis of hardness distribution is shown in Figure 14 , which depicts solid-state cladded coatings’ superiority over those cladded by traditional processes.…”
Section: Resultsmentioning
confidence: 99%
“…No significant deformation of the base substrate was found after the explosive detonation [ 75 , 78 ]. Lalu Gladson Robin et al reported that the coating layers cladded with the help of explosion cladding possess excellent hardness even at the coating-substrate interface [ 76 ]. A comparative analysis of hardness distribution is shown in Figure 14 , which depicts solid-state cladded coatings’ superiority over those cladded by traditional processes.…”
Section: Resultsmentioning
confidence: 99%